1999
DOI: 10.1038/sj.ejhg.5200285
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptance of screening for fragile X mutations in low-risk pregnancies

Abstract: Fragile X syndrome is the second leading cause of mental retardation after Down syndrome. Most women carriers of the fragile X mutation are unaware of their condition. We critically evaluated whether screening pregnant women at low risk for FMR1 mutation would be feasible as a routine part of antenatal care in general practice. We also studied acceptance and attitudes to gene testing. From July 1995 until December 1996, a carrier test was offered at the Kuopio City Health Centre free of charge to all pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
2
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 21 publications
4
94
2
2
Order By: Relevance
“…Follow-up interviews with a sub-group of women from this study revealed, however, that women had trouble relating to the clinical information about FXS and wanted to know more about families' experiences of FXS (Archibald et al 2009). No harms to psychological wellbeing have been demonstrated to date, although only three studies have specifically investigated the impact of offering screening on psychological factors such as anxiety (Ryynanen et al 1999;Fanos et al 2006;Metcalfe et al 2008).…”
Section: Carrier Screening For Fragile X Syndromementioning
confidence: 79%
See 1 more Smart Citation
“…Follow-up interviews with a sub-group of women from this study revealed, however, that women had trouble relating to the clinical information about FXS and wanted to know more about families' experiences of FXS (Archibald et al 2009). No harms to psychological wellbeing have been demonstrated to date, although only three studies have specifically investigated the impact of offering screening on psychological factors such as anxiety (Ryynanen et al 1999;Fanos et al 2006;Metcalfe et al 2008).…”
Section: Carrier Screening For Fragile X Syndromementioning
confidence: 79%
“…The majority were with pregnant women (Berkenstadt et al 2007;Cronister et al 2005;Fanos et al 2006;Huang et al 2003;Pesso et al 2000;Spence et al 1996;Ryynanen et al 1999;Toledano-Alhadef et al 2001;Kallinen et al 2001), while some included relatively smaller numbers of nonpregnant women (Pesso et al 2000;Spence et al 1996;Toledano-Alhadef et al 2001;Berkenstadt et al 2007;Geva et al 2000). Most studies essentially focused on the uptake of testing, with rates varying between 7.9% ) and 21% (Spence et al 1996) in the USA, 80% in Israel (Pesso et al 2000), and 85% (Ryynanen et al 1999) and 92% respectively in two Finnish studies (Kallinen et al 2001).…”
Section: Carrier Screening For Fragile X Syndromementioning
confidence: 99%
“…Dig-labeled DNA molecular weight Marker V (Roche Diagnostics) and a known size marker were used as size standards. Filters were hybridized overnight at 42°C in roller bottles (Isotemp; Fisher Scientific) in Dig Easy Hybridization Buffer (Roche Diagnostics) with a Dig-end-labeled oligonucleotide probe [(CGG) 10 ] and Dig-labeled pBR322 DNA. Filters were washed at room temperature, twice for 5 minutes with 2ϫ SSC/0.1% SDS (100 ml) and twice for 7 minutes in a larger volume (400 ml) with the same washing solution, followed by two washes of 25 minutes, each in 0.5ϫ SSC/0.1 SDS at 45°C.…”
Section: Southern Blot and Pcr Analysismentioning
confidence: 99%
“…The need for appropriate education and genetic counseling has been emphasized as has the importance of research exploring psychosocial impacts of such screening (Finucane et al 2012;Sherman et al 2005). Research indicates that population screening for FXS is generally perceived favorably by families and healthcare providers (Acharya and Ross 2009;Archibald et al 2013;Ryynanen et al 1999;Skinner et al 2003) as well as individuals offered screening in research contexts (Anido et al 2005(Anido et al , 2007Archibald et al 2009;Fanos et al 2006;Metcalfe et al 2008;Sherman et al 2005), and there appears to be a preference for screening offered before pregnancy (Acharya and Ross 2009;Archibald et al 2013;Skinner et al 2003). As carrier screening approaches have varied, there is no clear consensus on how best to deliver population-based carrier screening for FXS.…”
Section: Introductionmentioning
confidence: 99%